Історико-філософськi витоки неоміфологічного світогляду - Шарніна, М.В. (Культура народов Причерноморья, 2013)
У статті визначено вагому роль світоглядних підвалин у формуванні ціннісної картини світу
людини того чи іншого історичного часу. Неоміфологічні світоглядні цінності можуть стати
конструктивним елементом подолання кризових явищ глобалізації, повернути людину до духовних
витоків та дати гідну відповідь викликам сучасної цивілізації. Автор робить висновок про те, що
глибинною духовною основою культурної традиції виступає міфологічний світогляд, що розкриває
архетипний зміст світовідчуття сучасної людини. В статье определена важная роль мировоззренческих устоев в формировании ценностной
картины мира человека того или иного исторического времени. Неомифологические мировоззренческие
ценности могут стать конструктивным элементом преодоления кризисных явлений глобализации,
вернуть человека к духовным истокам и дать достойный ответ вызовам современной цивилизации.
Автор делает вывод о том, что глубинной духовной основой культурной традиции выступает
мифологическое мировоззрение, которое раскрывает архетипический смысл мироощущения
современного человека. The article defines a significant role in shaping the philosophical foundations of the value of world
picture for a person of this or that historical time. Neomythological ideological values can be a constructive
element in overcoming the crisis of globalization, to return man to this spiritual roots and give an adequate
response to the challenges of modern civilization. The critical state of culture makes a man to look for the new
ideological orientations. In the Postmodern period this search is also due to a special relationship to a tradition.
The author concludes that the deep spiritual foundation of cultural tradition stands for the mythological world
outlook that reveals the archetypal content of the attitude of a modern man to his time. One of the most
meaningful form of an appeal to tradition, the present return to the past is a myth and mythology as a system of
philosophical concepts and generalizations of the most archaic times actual at present. Neomythological outlook
is based on the revival of mythological consciousness, appeal to the unconscious sphere, as a necessary
condition of self-consciousness of a modern man, who is in search of his spirituality more often opens path back
to himself through a myth. Ukrainian myths, unlike German and Russian, are imbued with humour and
optimism, and folk mythology expresses the most typical mental picture of the nation.